A novel technique of arterial blood flow modification in intra-arterial chemoradiotherapy of maxillary sinus squamous cell carcinoma. (October 2020) - Kanno, Chihiro; Masubuchi, Tatsuo; Fushimi, Chihiro; Kitani, Yosuke; Niwa, Kazutomo; Takeishi, Etsuro; Kaneko, Tetsuharu; Yamazaki, Morio; Hasegawa, Hiroshi; Kamata, Shin-etsu; Miura, Kouki; Tada, Yuichiro
Highlights: Intra-arterial chemoradiotherapy is a useful treatment for maxillary sinus SCC. Ensuring proper drug delivery is a concern, as a tumor's blood supply is complex. Blood flow was fully altered to the maxillary artery by facial artery ligation. In all patients, planned treatment was realized; complete response was achieved. This method simplifies and standardizes the treatment and may improve outcomes. Abstract: Objectives: Intra-arterial chemoradiotherapy via a superficial temporal artery is reportedly a useful organ-preserving treatment for maxillary sinus squamous cell carcinoma. This study aimed to determine whether blood flow modification facilitates sufficient drug delivery to the entire carcinoma via the maxillary artery alone, even for advanced tumors. Materials and methods: A retrospective study of 10 patients who were diagnosed with locally advanced carcinoma (4 [40%] at stage T3, 5 [50%] at T4a, and 1 [10%] at T4b) from August 2016 to July 2018, with tumor blood flow from both the maxillary and facial arteries, was conducted. Patients underwent intra-arterial chemoradiotherapy, which involved chemotherapy with weekly cisplatin administration (40 mg/m 2 ) and radiotherapy (70 Gy/35 fr), with facial artery ligation. The success rate of blood flow modification, as well as its therapeutic effects and safety, were evaluated, with a median follow-up period of 14.4 months (range: 12.3–35 months). Results: The blood flow surrounding the tumor was changed from both the maxillary and facial arteries to the maxillary artery alone in all patients. A median of 9 chemotherapy courses (range: 8–10) were administered; the median total cisplatin dose was 350 mg/m 2 (range: 320–360 mg/m 2 ). Radiotherapy of 70 Gy/35 fr was used to treat all patients. Grade 3 oral mucositis (80%) and irradiation field dermatitis (40%) were observed. In all patients, complete response was achieved, and local recurrence was not observed for at least 1 year. Conclusion: Simplifying the blood flow around the tumor facilitates more standardized intra-arterial chemoradiotherapy via a superficial temporal artery procedure.